Academic e-books : publishers, librarians, and users - Ward, Suzanne M.; Freeman, Robert S.; Nixon, Judith M. (Charleston insights in library, archival, and information sciences., 2016)
"Academic E-Books: Publishers, Librarians, and Users provides readers with a view of the changing and emerging roles of electronic books in higher education. The three main sections contain contributions by experts in the publisher/vendor arena, as well as by librarians who report on both the challenges of offering and managing e-books and on the issues surrounding patron use of e-books. The case study section offers perspectives from seven different sizes and types of libraries whose librarians describe innovative and thought-provoking projects involving e-books. Read about perspectives on e-books from organizations as diverse as a commercial publisher and an association press. Learn about the viewpoint of a jobber. Find out about the e-book challenges facing librarians, such as the quest to control costs in the patron-driven acquisitions (PDA) model, how to solve the dilemma of resource sharing with e-books, and how to manage PDA in the consortial environment. See what patron use of e-books reveals about reading habits and disciplinary differences. Finally, in the case study section, discover how to promote scholarly e-books, how to manage an e-reader checkout program, and how one library replaced most of its print collection with e-books. These and other examples illustrate how innovative librarians use e-books to enhance users' experiences with scholarly works"--